Monopolizing Sanctioning Power under Noise Eliminates Perverse Punishment But Does Not Increase Cooperation - Fischer, Sven; Grechenig, Kristoffel; Meier, Nicolas (Frontiers in Behavioral Neuroscience, 2016)
We run several experiments which allow us to compare cooperation under perfect and imperfect information in a centralized and decentralized punishment regime. Under perfect and extremely noisy information, aggregate behavior does not differ between institutions. Under intermediate noise, punishment escalates in the decentralized peer-to-peer punishment regime which badly affects efficiency while sustaining cooperation for longer. Only decentralized punishment is often directed at cooperators (perverse punishment). We report several, sometimes subtle, differences in punishment behavior, and how contributions react.